A simulation-based decision support for eco-efficiency improvements in production systems. (15th October 2015) - Sproedt, A.; Plehn, J.; Schönsleben, P.; Herrmann, C.
Abstract: Environmental sustainability is an everlasting concern of our modern society and has been gaining importance in practice and academia over the last decades. For being a major contributor to global environmental pollution, stakeholder pressure on manufacturing companies is increasing to reduce their environmental impacts, while simultaneously delivering high value goods and services at competitive prices, understood as increasing their eco-efficiency. However, complex interrelations between the economic and environmental performance dimensions in production systems create a non-transparency to decision makers, hindering them to translate this strategic target into improvement measures on a shop-floor level. Discrete-event simulation has been established as a promising method to solve this problem, although current approaches are insufficient for focusing only on energy aspects and being too complex in their application. This paper proposes a decision support consisting of two elements: 1) A novel discrete-event simulation approach that seamlessly integrates LCA with common economic evaluations by embedding the Ecoinvent LCI database, while considering all relevant eco-efficiency drivers within a production system; and 2) a system analysis and modelling procedure supporting its application and the identification of appropriate improvement measures.